LEVERAGING THE ELECTRONIC MEDICAL RECORD TO REDUCE THE RATE OF HOSPITAL ACQUIRED CLOSTRIDIUM DIFFICILE AT AN ACADEMIC SAFETY NET HOSPITAL. Issue 12 (18th November 2016) - Gregson, Deborah; Burke, Robert; Miller, Nancy S.; Ostrander, Thomas; Jawa, Raagini; Phull, Pooja; Scanlon, Katherine; Fleming, Kelly; Bradley, Matthew; Steinke, Jeremy; Jung, Youngjin; Pierre, Cassandra
Abstract : Background: Clostridium difficile infections (CDI) are the leading cause of health care-associated diarrhea, and is reported to cause 500, 000 patient infections in the United States per year. A target for reducing the number of CDIs have been established by the Centers for Medicare and Medicaid Services (CMS). Boston Medical Center's reported CY2013 Standardized Infection Ration (SIR) for Hospital Onset CDI was 1.573, above the US National Benchmark of 1. Objectives: Reduce the SIR Hospital Onset C. difficile to CMS expected ratio of =1 by June, 2016. Methods: Using Quality Improvement methodologies a multidisciplinary team addressed the appropriateness of CDI PCR testing and increased patient isolation through the use of the electronic medical record. PDSAs included: The CDI order was modified to include instructions on appropriate test frequency and sample consistency. Past lab results are displayed within the order as an automated reminder. A Best Practice Alert "fires" when writing an order if a laxative has been administered within the past 72 hours, recommending that the laxative is discontinued prior to testing Created a CDI testing and Contact Plus Isolation order panel to reduce the risk of environmental contamination. Negative lab results include instructions to discontinue isolation. Results: Decreased test volume by 39%; reduced inappropriate repeat testing by 80%, 7 day negative and 66%, 30 day positive. Achieved SIR 4 quarter average 0.78, better than national goal. Conclusions: Through the use of QI and leveraging changes in the eMAR improves appropriate testing and patient isolation reducing the risk of hospital acquired CDI.Figure 1 Figure 2 Figure 3 Figure 4